Relationships between calciemia and calciuria and EEG and HRV parameters in patients with chronic pyelonephritis - Anatoliy Gozhenko; Anatoliy Kushneruk; Walery Zukow; Igor Popovych (Kazimierz Wielki University, 2020)
Background. This article launches a new project "Relationships between parameters of electrolytes exchange and EEG&HRV in people without kidney disease and patients with chronic pyelonephritis". Calcium was chosen as the first swallow. Material and methods. The object of observation were 48 males and 15 females 24-76 years old, who came to the spa Truskavets' (Ukraine) for the treatment of chronic pyelonephritis in remission. We recorded simultaneosly EEG ("NeuroCom Standard") and electrocardiogram ("CardioLab+HRV") in II lead to assess the parameters of HRV. Calcium and creatinine concentration was determined in blood plasma and daily urine. Results. The observed sample is characterized by moderate and mild expressed urinary syndrome, ie represents the urological contingent of the Truskavets' spa. It was stated normal or moderately reduced plasma calcium levels in combination with a very wide range of calcium urinary excretion. A very strong canonical correlation was found between calciumemia and EEG/HRV parameters (r=0,910). The correlation with the parameters of the beta rhythm of the EEG and VLF/ULF components of the HRV is positive, while with the parameters of the alpha rhythm of the EEG is negative. The canonical correlation between calciumuria and EEG/HRV parameters is moderate (r=0,571). There was a positive correlation with other parameters of the beta rhythm of the EEG and a negative correlation with the parameters of the delta rhythm of the EEG and LF/VLF components of HRV. Conclusion. Parameters of calcium exchange and EEG/HRV are closely related, however the question of the causal nature of correlations remains open.